Ketidakadilan Gender pada Pernikahan dalam “Perempuan Patah Hati yang Kembali Menemukan Cinta Melalui Mimpi” Karya Eka Kurniawan - Anindya Kusuma Wardani; Maria Benga Geleuk (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2020)
Marriage is a sacred, religious, and has long-term purposes activity. Marriage is assumed as making a legal relationship between a couple within opposite sex. Rather than being a simple activity, marriage is a complex activity which has various aims that are teaching and taking care children, working together with the couple, and other happiness purposes. However, this picture of marriage seems missing in the work of Eka Kurniawan in the book of Perempuan Patah Hati yang Kembali Menemukan Cinta Melalui Mimpi. Through this book, the readers can see the opposite condition of marriage compared to marriage’s stereotypes within the society. It also shows there are gender inequality practices throughout the story. Using Critical Feminism theory and descriptive-qualitative method, this research purpose is to analyze three short stories by Eka Kurniawan entitle (1) Gincu ini Merah, Sayang, (2) Cerita Batu, and (3) Pelajaran Memeliharan Burung Beo, to find how gender inequality depicted and the portrait of marriage which in the short stories. These three short stories show similar problem in a marriage which resulted in divorce. Through the process, this study found two main portraits of marriage in the works of Eka Kurniawan, that are (1) in marriage there are gender inequality practices which makes women suffer in various areas. (2) The relationship between male and female characters shows an unhealthy relationship in which women always suffers. Both result shows that marriage is not always about happiness, but its face has been changed due to unhealthy relationship. In all unhealthy marriage, woman always captures as the victims which legitimizing woman position as a submissive in a relationship even in the modern society.